(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Nowadays, a lot of new active substances as antiepileptic agents have been developed. One of the protein targets of antiepileptic is selective GABA. Selective GABA is the regulator of CNS activity. In this research, quinazolinone derivatives were used to design the antiepileptic agent through a selective GABA activation. The potential activity of quinazolinone derivatives could be increased by substitution in position 3 of quinazolinone. Molecular docking of selective GABA activation was required to predict their antiepileptic activity. The molecular docking of quinazolinone derivatives was carried out using Autodock viva Ver.1.1.2. Twenty quinazolinone derivatives were docked into GABAa with PDB code 4cof. The interaction was evaluated based on the docking score. Diazepam was used as the reference standard for this research. Twenty quinazolinone derivatives showed the approximate docking score -7.1 to -9.3 kcal/mol. All twenty quinazolinone derivatives which value that have greater docking score compared to diazepam used as a standard compound. Derivative Q-18 had higher binding energy than other quinazolinone derivatives because it has the smallest docking score. All new quinazolinone derivatives are feasible to be synthesize and performed their in vitro evaluation.